Pengaruh Kehandalan Dan Brand Image Terhadap Kepuasan Konsumen Dalam Penggunaan Digital Payment Dana (Studi Pada Mahasiswa FEB Universitas Muhammadiyah Metro) - Septiana, Nani; Nasikah, Durotun; Wulandari, Tri Wahyu (Jurnal Manajemen DIVERSIFIKASI, 2023)
The development of information and communication technology makes all human activities easier both in the economic and social fields. In today's technological developments, new innovations are needed so that all human activities become more efficient, safe, fast and comfortable, especially in the world economy. Digital wallets are electronic applications that can be used to pay for online transactions. This study aims to determine 1) To determine the effect of reliability on Consumer Satisfaction in the Use of Digital Payments (Dana). 2) To determine the effect of brand image on Consumer Satisfaction in the Use of Digital Payments (Dana). 4) To determine the effect of reliability, brand image on Consumer Satisfaction in the Use of Digital Payments (Funds). The survey method was chosen as the primary data source. The survey method focuses on collecting data from respondents who have certain information, thus enabling researchers to solve problems. Data collection was carried out using a questionnaire or questionnaire instrument. In this study, the population is consumers who use Telkom products. The sampling technique uses accidental sampling with a total sample of 72 people. Data collection techniques using a questionnaire with a Likert scale. The results of the study show that 1) there is a positive and significant influence between reliability on Consumer Satisfaction in the Use of Digital Payments (Funds). 2) there is a positive and significant influence between brand image on consumer satisfaction in the use of digital payments (funds). 4) there is a positive and significant influence between reliability, brand image on consumer satisfaction in the use of digital payments (funds).